MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SISWA KELAS IV B DENGAN MENGGUNAKAN MODEL CONCEPT SENTENCE PADA TEMA PEMBELAJARAN “INDAHNYA KEBERSAMAAN” SEMESTER 1 SD NEGERI 1 CURAH JERU KECAMATAN PANJI KABUPATEN SITUBONDO TAHUN PELAJARAN 2015/2016 - Mahfudha Yuli Nurriskiyah; Nur Holifatuz Zahro (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
Learning activities learning in SDN 1 Curah Jeru less increase skills, particularly writing skills learning on the theme of the exposition essay "Beauty Togetherness". It caused during these teachers only use conventional methods because of a lack of creativity/lecture from the teacher. Teachers use media that are less attractive for students that is the only image in the students so that students feel saturated and not interested in learning to write the story/essay correctly according the rules of the writing of the essay. Model learning Concept Sentence is one type of learning model developed from cooperative learning. According to Shoimin (2001:37) Concept Sentence (Sentence concept) is a model of learning which is done by giving the cards that contains some key words to students. These keywords are then organized into paragraphs-paragraphs. This model is done with students formed a group of heterogeneous and make a sentence with at least 4 keywords match the material being presented. This research was carried out in class IV B SDN 1 Curah Jeru consisting of 27 students. Students are organized into 5 groups are heterogeneous. This type of research is research class action done 2 cycles. Method of collecting data through observation, interviews, tests/tasks, and documentation. The percentage of implementation of the learning model concept sentence on cycle I reached 68% and cycle II reached 87%. On cycle I, the percentage of ketuntasan in writing skills bouquet of 67% in the category of skilled enough, while on cycle II amounted to 89% in the category of very skilled, so classical meets the Minimum Completely Criteria (KKM) SDN 1 Curah Jeru. Conclusion of this research is to increase students writing skills bouquet of Exposition. The increase in the percentage of students of essay writing skills I cycle to cycle II amounting to 22%, while the increase in the application of the model concept sentence from cycle to cycle I II of 19%. Conclusion of this research is to increase students ' writing skills bouquet of Exposition. The increase in the percentage of students of essay writing skills I cycle to cycle II amounting to 22%, while the increase in the application of the model concept sentence from cycle to cycle I II of 19%. Therefore research SDN 1 Curah Jeru completely